Computed Tomography-Based Image-Guided System in Spinal Surgery: State of the Art Through 10 Years of Experience. Issue 1 (19th January 2015) - Costa, Francesco; Dorelli, Gianluigi; Ortolina, Alessandro; Cardia, Andrea; Attuati, Luca; Tomei, Massimo; Milani, Davide; Balzarini, Luca; Galbusera, Fabio; Morenghi, Emanuela; Fornari, Maurizio
Abstract: BACKGROUND: Image-guided navigation systems (IGS) grant excellent clinical and radiological results, minimizing risks correlated with spinal instrumentation. However, there is some concern regarding the real need for IGS and its indications. OBJECTIVE: To analyze the accuracy, technical aspect, and radiation exposure data of the principal IGS based on computed tomography (CT) imaging. METHODS: The data of all patients treated for spinal instrumentation with the aid of an IGS system from January 2003 to March 2013 were retrospectively analyzed. We defined 2 groups: group I with an IGS system based on a preoperative CT scan; group II relied on an intraoperative CT scan. Screw accuracy was assessed with a postoperative CT scan control. Radiation dosage for patients was defined by using the technical parameters and dose report data. Statistical analysis was performed using the Fisher exact test with a significance of 5% ( P value < .05). RESULTS: Two thousand twenty patients and 11 144 screws were analyzed. Group I had 794 patients (4246 screws); the accuracy was 96.1%. Group II had 1226 patients (6898 screws) treated, with 98.5% accuracy ( P = .001). The radiation dose analysis showed better results in group II, with significant reduction of the effective dose to the patient. CONCLUSION: The IGS based on an intraoperative CT scan grants excellent results, eliminating the rate of reoperation for misplaced instrumentations (screws, plate, and cage) or for inadequate bone decompression. However, this technology cannot replace the surgical skills, experience, and knowledge necessary for spine surgery.